2014
DOI: 10.1007/s10797-014-9345-9
|View full text |Cite
|
Sign up to set email alerts
|

Tax rates as strategic substitutes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 37 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…Strategic complementary is the more instinctive assumption, but is not theoretically assured. Vrijburg and de Mooij (2016), in particular, show that the response to a tax increase abroad, leading to an inflow of investment and hence an increase in domestic revenue, may to be reduce the domestic tax rate if the degree of substitutability between the domestic public good and private consumption is sufficiently low. Empirically, however, as surveyed in Brueckner (2003), Leibrecht and Hocgatterer (2012) and most recently OECD (2020), 10 the weight of evidence suggests that statutory corporate tax rates-the most relevant for profit shifting concerns here-are strategic complements.…”
Section: When Is a 'Modest' Minimum Tax Pareto-improving?mentioning
confidence: 99%
“…Strategic complementary is the more instinctive assumption, but is not theoretically assured. Vrijburg and de Mooij (2016), in particular, show that the response to a tax increase abroad, leading to an inflow of investment and hence an increase in domestic revenue, may to be reduce the domestic tax rate if the degree of substitutability between the domestic public good and private consumption is sufficiently low. Empirically, however, as surveyed in Brueckner (2003), Leibrecht and Hocgatterer (2012) and most recently OECD (2020), 10 the weight of evidence suggests that statutory corporate tax rates-the most relevant for profit shifting concerns here-are strategic complements.…”
Section: When Is a 'Modest' Minimum Tax Pareto-improving?mentioning
confidence: 99%
“…A similar result can be obtained if jurisdictions use public spending (instead of taxes) as their relevant strategic tool (see e.g., Wildasin, 1988). 4 More recently, Vrijburg and de Mooij (2016) have shown that the slope of reaction functions depends on the jurisdiction's objective function. If countries maximize tax revenues, the slope of reaction functions is always positive; on the other hand, if jurisdictions maximize welfare, a negative slope (reecting the fact that tax rates are strategic substitutes) can be obtained with realistic parameter values.…”
Section: Introductionmentioning
confidence: 53%
“…Our model allows us to interpret the results of the previous literature in a new light. For example, Vrijburg and de Mooij (2016) concludes that with a linear welfare function, strategic complementary always holds. We show that this is true only if there are no spillovers.…”
Section: Reaction Functionsmentioning
confidence: 99%
“…A similar result can be obtained if jurisdictions use public spending (instead of taxes) as their relevant strategic tool (see, for example, Wildasin 1988). 2 More recently, Vrijburg and de Mooij (2016) have shown that the slope of the reaction functions depends on the jurisdiction's objective function. If countries maximize tax revenues, the slope of the reaction functions is always positive; on the other hand, if jurisdictions maximize welfare, a negative slope (denoting that tax rates are strategic substitutes) can be obtained.…”
Section: Introductionmentioning
confidence: 99%